DIGITAL HEALTH LITERACY AND CANCER MISINFORMATION/DISINFORMATION IN BRAZIL: IMPLICATIONS FOR SCIENTIFIC DISSEMINATION IN NUCLEAR MEDICINE AND ONCOLOGY - ROMULO SANTANA OSTHUES; Elba Cristina Sá de Camargo ETCHEBEHERE; Barbara Juarez AMORIM; Carmino Antonio DE SOUZA; Larissa Mansano DE SOUZA; Amira Al DERGHAM (Hematology, Transfusion and Cell Therapy)
Summary: The study investigates digital health literacy and misinformation/disinformation related to cancer, with an emphasis on understanding the obstacles to scientific dissemination about nuclear technologies applied in the Theranostic model. This model, which integrates diagnosis and treatment through radiopharmaceuticals, has the potential to significantly improve the care of Oncology patients by directing radiation precisely to tumor tissue, thereby minimizing side effects. However, the complexity of innovations such as those present in Theranostics poses challenges for scientific dissemination, especially in a scenario where misinformation/disinformation, denialism, and pseudoscience are becoming increasingly frequent, influencing the public perception of the safety and efficacy of medical approaches. Various studies indicate that low health literacy can lead to the spread of erroneous information and an increase in prejudice and distrust, negatively impacting adherence to modern therapies and communication between physicians and patients. The literature review shows that media companies frequently prioritize sensationalist and stereotyped topics about nuclear technology, while reliable information is neglected. Moreover, research indicates disparities in digital health literacy among different population groups, highlighting the need for new strategies to formulate educational campaigns and scientific dissemination actions that strengthen access to evidence-based information, thereby contributing to the improvement of patients' quality of life and the reinforcement of health systems. In view of this scenario, the application of an online questionnaire, based on the adapted version of the eHealth Literacy Scales (eHEALS), is imperative to measure the hypotheses regarding individuals’ ability to seek, understand, and use reliable information about cancer and the nuclear technologies involved in diagnostic and therapeutic procedures with radiopharmaceuticals, as well as to identify the main channels and sociodemographic factors that may influence the dissemination of misleading content. Conclusion: As a result of the literature review, it was found necessary to improve the population's digital health literacy and combat misinformation/disinformation related to cancer, especially regarding the use of nuclear technology for diagnostic and therapeutic purposes — particularly through the radiopharmaceuticals used in Nuclear Medicine. The application of the proposed questionnaire in the Brazilian scenario will allow the identification of barriers and gaps in understanding the benefits of the Theranostic model, providing support for the development of educational strategies and scientific dissemination actions promoted by the Knowledge Dissemination team of CEPID CancerThera. These actions are fundamental to popularize access to knowledge, reduce the negative impact of misinformation/disinformation, and promote safer and more effective oncological approaches, such as Theranostics.